Feeding habits of fishes in the Pengkalan Gawi–Pulau Dula Section of Kenyir Lake Terengganu, Malaysia - Abdul Satar, Mustafa Kamal; Kamaruddin, Izharuddin Shah; Christianus, Annie; Daud, Siti Khalijah; Lirong, Yu Abit (Asian Fisheries Society, 2012)
A study was conducted to determine the feeding habits of the fish in the Pengkalan Gawi–Pulau Dula section of Kenyir Lake, Terengganu, Malaysia. Fish were collected on a monthly basis from February 2008 to January 2009 and their stomach contents were identified and quantified. A total of 261 individual fish from 6 different species were captured and the sample size of each species ranged from between 10 to 98 individuals. Aquatic insects were the most abundant among food items consumed. Four species namely, Barbodes schwanenfeldii (Bleeker, 1853), Notopterus sp., Hampala macrolepidota, Kuhl and van Hasselt, 1823, and Pristolepis fasciatus (Bleeker, 1851) were classified as omnivorous species, whereas Hemibagrus nemurus (Valenciennes, 1840) was classified as insectivorous and Channa micropeltes (Cuvier, 1831) was classified as piscivorous. The feeding habits of the three most dominant species were found to differ spatially and temporally. A more complex feeding habit was observed in the Pulau Pupi station and changes in feeding guilds were observed at each season throughout the study period.